Determination of citrate content in specialty paper based on headspace gas chromatography - Qiyu He; Baoshan Yue; Xinruitong Liu; Hongyue Zhu; Zhenhua Yu; Ying Zhang; Cong Gao; Wei Chen; Yingchun Luo; Jiao Xie; Yi Dai (Frontiers in Chemistry, 2025)
A method for determining citrate content in specialty paper using headspace gas chromatography (HS-GC) is proposed. This method is based on the reaction between sodium citrate and potassium permanganate under acidic conditions, which generates CO2. The CO2 is detected by a thermal conductivity detector and the sodium citrate content is calculated using a standard curve. Optimization of the method was conducted by investigating various parameters, including gas chromatography conditions, equilibrium time, equilibrium temperature, and injection volume. The method’s accuracy and precision were assessed through method validation. The results demonstrated that the relative standard deviation (RSD) was ≤3.00%, and the recovery rate ranged from 91% to 102%, indicating good reliability and accuracy. This method is simple, rapid, and precise, making it an effective approach for the determination of citrate content in specialty paper.